Clinical researchIncidence of mortality in 1,040 patients with coronary heart disease or hypertensive heart disease with normal and abnormal left ventricular ejection fraction and with normal and abnormal QRS duration - Lai, Hoang M.; Aronow, Wilbert; Rachdev, Archana; Asija, Amit; Lai, Khanh V.; George, Jerry; McClung, John A. (Archives of Medical Science, 2008)
Introduction: The QRS duration on the resting ECG and LVEF determined by 2-dimensional echocardiography were measured in 1,040 patients with coronary heart disease or hypertensive heart disease with left ventricular hypertrophy (LVH). Material and methods: A QRS duration of ³120 msec was considered abnormal. A LVEF <50% was considered abnormal. The 1,040 patients included 627 men and 413 women, mean age 66±15 years. All-cause-mortality was determined at follow-up. Results: Mean follow-up was 17±10 months. Death occurred in 65 (11%) of 598 patients with a normal QRS duration and a normal LVEF[1], in 19 (19%) of 100 patients with an abnormal QRS duration and a normal LVEF[2], in 53 of 242 (22%) patients with a normal QRS duration and an abnormal LVEF[3], and in 36 (36%) of 100 patients with an abnormal QRS duration and an abnormal LVEF[4] (P<0.025 comparing 1 with 2, P<0.001 comparing 1 with 3 and 1 with 4, P<0.01 comparing 2 with 4 and 3 with 4). Conclusions: Patients with coronary heart disease or hypertensive heart disease with LVH and an abnormal LVEF and an abnormal QRS duration had a significant 3.3 times higher mortality than patients with coronary heart disease or hypertensive heart disease with LVH and a normal LVEF and a normal QRS duration.